PENGARUH KNOWLEDGE SHARING DAN PEMBERDAYAAN TERHADAP KINERJA PERANGKAT DESA DI KECAMATAN DANAU KERINCI BARAT DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Afrianti, Fitrina; Hafiz, Adrul; Siswadhi, Ferry; Lestari, Anggia Ayu (Jurnal Ekonomi Sakti, 2024)
This research aims to find out: 1) To what extent is the influence of knowledge sharing on the satisfaction of village officials in West Lake Kerinci sub- district?, 2) To what extent is the influence of empowerment on job satisfaction of village officials in West Lake Kerinci sub-district? the performance of village officials in West Lake Kerinci sub-district directly or indirectly? 4) To what extent does empowerment influence the performance of village officials in West Lake Kerinci sub-district, both directly and indirectly? 5) To what extent does job satisfaction influence the performance of village officials in West Lake Kerinci sub- district. The population in this study was the entire village apparatus in West Lake Kerinci sub-district, 140 people. Furthermore, by using the Slovin formula, a sample size of 42 respondents was obtained using the Proportional Random Sampling sampling technique. The data analysis tool used is path analysis at an alpha level of 0.05. Based on the research results, it shows that: Knowledge sharing has a negative and significant effect on job satisfaction, empowerment has a positive and significant effect on job satisfaction. Both directly and indirectly, knowledge sharing has a negative and significant effect on performance. Both directly and indirectly, empowerment has a positive and significant effect on performance. Job satisfaction has a negative and significant effect on performance.